PENGARUH WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA (STUDI PADA DI RS X YANG TERDAPAT DI PONOROGO) - Hanggara, Dino Ichsandy (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The hospital is one of the health facilities that has an important role in providing health services to the community. The quality of hospital service is heavily influenced by the performance of the staff. One factor that affects employee performance is work-life balance. RSU X yang berada di Ponorogo is a private hospital that operates in the field of health services. RSU x yang berada di Ponorogo has several services available including hospital care, street care, medical care, CT scan as well as hemodialysis therapy. The aim of this study is to test and analyze the impact of work life balance on employee performance through job satisfaction at RSU x yang berada di ponorogo. This research is quantitative. The sampling technique uses a saturated sample with a purposive sample type where the sample has been determined by a researcher with a specific weighting with a number of respondents of as many as 85 nurses at Darmayu Ponorogo RSU. The statistical analysis used in this study is partial least square (PLS) with the help of SmartPLS 3.2.9 software. The results of this study explained that work life balance had a positive and significant impact on employee performance, work life equilibrium had a significant and positive impact on job satisfaction, employee's performance had a negative and significant influence on employment satisfaction and employee satisfaction was able to mediate the relationship between work life balances and employees' performance.